Probabilistic Integrated Human Mixture Risk Assessment of Multiple Metals Through Seafood Consumption. Issue 2 (3rd September 2018) - Lin, Yi‐Jun; Lin, Pinpin
Abstract: Inorganic arsenic (iAs), cadmium (Cd), lead (Pb), and methylmercury (MeHg) are toxic metals that cause substantial health concern and are present in various seafood items. This study linked probabilistic risk assessment to the interactive hazard index (HIINT ) approach to assess the human mixture risk posed by the dietary intake of iAs, Cd, Pb, and MeHg from seafood for different age populations, and joint toxic actions and toxic interactions among metals were also considered in the assessment. We found that, in combination, an iAs–Cd–Pb–MeHg mixture synergistically causes neurological toxicity. Furthermore, an iAs–Cd–Pb mixture antagonistically causes renal and hematological effects and additively causes cardiovascular effect. Our results demonstrated that if toxic interactions are not considered, the health risk may be overestimated or underestimated. The 50th percentile HIINT estimates in all age populations for neurological, renal, cardiovascular, and hematological effects were lower than 1; however, the 97.5th percentile HIINT estimates might exceed 1. In particular, toddlers and preschoolers had the highest neurological risk, with 0.16 and 0.19 probabilities, respectively, of neurological HIINT exceeding 1. Saltwater fish consumption was the principal contributor to the health risk. We suggest that regular monitoring of metal levels in seafood, more precise dietary surveys, further toxicological data, and risk–benefit analysis of seafood consumption are warranted to improve the accuracy of human mixture risk assessment and determine optimal consumption.